PERBANDINGAN ESTIMASI DURASI PROYEK KONSTRUKSI BAJA LIMA LANTAI DENGAN METODE EVM, ES, ED, DAN TVA - Alexander Irawan; Arianti Sutandi (JMTS: Jurnal Mitra Teknik Sipil, 2026)
The success of a construction project depends on the control of cost, quality, and time. The earned value management (EVM) method is widely used, but it measures schedule performance in cost units, making its time prediction less accurate. As alternatives, the earned schedule (ES), earned duration (ED), and three-variance approach (TVA) methods were developed. This study compares the duration prediction accuracy of these four methods on a five-story steel shop house construction project on Jalan Setiabudi, Bandung. The performance indicators of each method were calculated from the first to the twenty-second week, then the duration estimates were compared against the actual duration to obtain the mean absolute percentage error (MAPE). The TVA Scheduled method produced the smallest deviation of 28.72%, followed by ES at 30.10%, ED at 34.29%, and both EVM and TVA Planned at 36.25%, all in the Reasonable category. TVA Scheduled, which uses the local work rate between consecutive weeks, adapts best to the earned value spikes of steel structural work, while EVM remains useful for cost control and infrastructural development. Abstrak Keberhasilan proyek konstruksi bergantung pada pengendalian biaya, mutu, dan waktu. Metode earned value management (EVM) umum dipakai, tetapi mengukur kinerja jadwal dalam satuan biaya sehingga prediksi waktunya kurang akurat. Sebagai alternatif, dikembangkan metode earned schedule (ES), earned duration (ED), dan three-variance approach (TVA). Penelitian ini membandingkan akurasi prediksi durasi keempat metode pada proyek konstruksi baja ruko 5 lantai di Jalan Setiabudi, Bandung. Indikator kinerja tiap metode dihitung dari minggu pertama hingga minggu ke-22, lalu estimasi durasinya dibandingkan terhadap durasi aktual untuk memperoleh nilai mean absolute percentage error (MAPE). Hasilnya, metode TVA Scheduled menghasilkan simpangan terkecil sebesar 28,72%, diikuti ES 30,10%, ED 34,29%, serta EVM dan TVA Planned masing-masing 36,25%, seluruhnya tergolong kategori reasonable. Metode TVA Scheduled yang memakai laju kerja lokal antarminggu paling adaptif terhadap lonjakan earned value pada pekerjaan struktur baja sehingga paling akurat, sedangkan EVM tetap berguna untuk pengendalian biaya dan pengembangan infrastruktur.